A sociological reflection on sound, language and music - Sanchez Aguirre, Rafael Andres (2015)
The reflection on the relation between sound, language and music is necessary to clarify how these concepts are connected with “dimensions and senses of collectivity”. In a panoramic and introductory way, this paper tries to explore the social long-process constituted from the “unarticulated” human sounds that serve as a base to an articulated (musical) language and a simultaneous generation of music. The main objective consists in clarifying some central topics for sociology of music. The argumentation presents each concept in interdependence with the others and recurs to a process-sociological perspective. Thus, sound, language and music are particularly thought in connection with their social function and not only as an esthetical, physical or philosophical phenomenon.